Co-Occurrence and Levels of Mycotoxins in Fish Feeds in Kenya - Mwihia, Evalyn Wanjiru (Toxins (Basel), 2020)
This study determined the presence, levels and co-occurrence of mycotoxins in fish feeds in Kenya. Seventy-eight fish feeds and ingredients were sampled from fish farms and fish feed manufacturing plants and analysed for 40 mycotoxins using high-performance liquid chromatography-high resolution mass spectrometry. Twenty-nine (73%) mycotoxins were identified with 76 (97%) samples testing positive for mycotoxins presence. Mycotoxins with the highest prevalences were enniatin B (91%), deoxynivalenol (76%) and fumonisin B1 (54%) while those with the highest maximum levels were sterigmatocystin (<30.5–3517.1 µg/kg); moniliformin (<218.9–2583.4 µg/kg) and ergotamine (<29.3–1895.6 µg/kg). Mycotoxin co-occurrence was observed in 68 (87%) samples. Correlations were observed between the fumonisins; enniatins B and zearalenone and its metabolites. Fish dietary exposure estimates ranged between <0.16 and 43.38 µg/kg body weight per day. This study shows evidence of mycotoxin presence and co-occurrence in fish feeds and feed ingredients in Kenya. Fish exposure to these levels of mycotoxins over a long period of time may lead to adverse health effects due to their possible additive, synergistic or antagonist toxic effects. Measures to reduce fish feed mycotoxin contamination should be taken to avoid mycotoxicosis in fish and subsequently in humans and animals through residues.